Voronoi Diagram Applications Towards New Sustainable Architectural Language - Adel Abbas (Journal of Engineering Research - Egypt)
This paper is concerned with the study of how to generate irregular geometric shapes that simulate their counterparts in nature, based on mathematical rules, specifically through Voronoi diagram, which already has been used in a group of contemporary buildings and urban design projects. The paper deals with this diagram through a theoretical study that explains the characteristics and applications of this diagram, with a review of examples of engineering formations that exist in nature and to which the applications of the Voronoi diagram apply. The paper aims to how to achieve a balance between form and function through this diagram, by studying and analyzing a group of contemporary buildings whose design was based on this diagram, whether in shaping the facades, forms and the structural systems.